2006
DOI: 10.1080/13506280500195292
|View full text |Cite
|
Sign up to set email alerts
|

Why don't we see changes? The role of attentional bottlenecks and limited visual memory

Abstract: Seven experiments explore the role of bottlenecks in selective attention and access to visual shortterm memory in the failure of observers to identify clearly visible changes in otherwise stable visual displays. Experiment One shows that observers fail to register a color change in an object even if they are cued to the location of the object by a transient at that location as the change is occurring. Experiment Two shows the same for orientation change. In Experiments Three and Four, attention is directed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
75
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 46 publications
7
75
2
Order By: Relevance
“…Previous studies have demonstrated that in visual search and change detection experiments, identification is dependent on localization (Treisman & Gelade, 1980;Treisman & Gormican, 1988;Dukewich & Klein, 2009;Ghorashi et al, 2010;Busch et al, 2010a;Schneider & Wascher, 2013;Chan & Hayward, 2009;Watanabe, 2003;Wolfe et al, 2006;Agostinelli et al, 1986;Becker et al, 2000;Hughes et al, 2012). Thus, Experiment 2 investigated whether change detection without localization also implies a failure to identify the changing feature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated that in visual search and change detection experiments, identification is dependent on localization (Treisman & Gelade, 1980;Treisman & Gormican, 1988;Dukewich & Klein, 2009;Ghorashi et al, 2010;Busch et al, 2010a;Schneider & Wascher, 2013;Chan & Hayward, 2009;Watanabe, 2003;Wolfe et al, 2006;Agostinelli et al, 1986;Becker et al, 2000;Hughes et al, 2012). Thus, Experiment 2 investigated whether change detection without localization also implies a failure to identify the changing feature.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies have investigated whether or not detection, localization, and recognition can be dissociated experimentally in visual search tasks or change detection tasks. Some of these studies found a dissociation of detection, localization, or recognition (Treisman & Gelade, 1980;Treisman & Gormican, 1988;Dukewich & Klein, 2009;Ghorashi et al, 2010;Busch et al, 2010a;Busch et al, 2010b;Schneider & Wascher, 2013;Chan & Hayward, 2009;Watanabe, 2003;Wolfe et al, 2006;Agostinelli et al, 1986;Becker et al, 2000;Turatto & Bridgeman, 2005;Hughes et al, 2012) while others found them to be similar (Luck & Vogel, 1997;Green, 1992;Joseph et al, 1997;Busey & Palmer, 2008;Zehetleitner & Müller, 2010) or found recognition to be conditional upon localization Donk and Meinecke (2001). Thus, whether target detection in visual search for static patterns can occur in the absence of localization or object recognition is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Pilling and Gellatly (2013) observed similar effects using a different type of VSTM task: an abrupt-probe task (Pilling & Gellatly, 2011;Wolfe et al, 2006). In the task, participants viewed a display containing from nine to 36 colored shapes.…”
mentioning
confidence: 83%
“…One possibility is that attention affects encoding processes. Attention is generally considered the Bgatekeeperf or VSTM; indeed, spatial attention seems to be a prerequisite for items to become encoded into VSTM (Averbach & Coriell, 1961;Awh, Vogel, & Ohr, 2006;Sperling, 1960;Wolfe, Reinecke, & Brawn, 2006). However, other evidence has shown that directions of spatial attention can influence VSTM even after encoding has taken place; cues presented during the retention interval also have a reliable effect on performance.…”
mentioning
confidence: 99%
“…One of the challenges of integrating visual information is the inability of the visual system to process all information simultaneously (Wolfe, 1994). Selection of visual information is therefore crucial as we are only able to attend to a small amount of information at any given time and unattended information is lost (Wolfe, Reinecke, & Brawn, 2006). Loss of information can occur during different stages of visual processing and is especially true whilst executing a saccade.…”
mentioning
confidence: 99%